Implications of meaninglessness in anxiety - Antonescu, Florena; Sandu, Mihaela Luminita (Technium Social Sciences Journal, 2023)
The purpose of this paper is to analyze from an existential point of view the sources of anxiety and depression of modern man.Over time, both anxiety and depression have been lived and approached as one of the individual's maladaptations to the outside world, as its inability to create a balance between the outside world and the inner world. Every citizen of our society realizes, based on his own experience as well as by observing his peers, that anxiety and depression are ubiquitous.We are becoming more and more aware not only of the obvious situations of creating anxiety and depression today, such as the threats of war, the uncontrolled atomic bomb and of the radical political and economic upheavals but also of the least obvious but extremely profound, namely inner confusion, psychological disorientation and uncertainty about acceptable standards of conduct.Despite the fact that anxiety and depression have become a central issue in some of the cultural dimensions of our existence, often, addressing the issues has been hampered by a lack of coordination between these theories and approaches. In this sense, one of the remarkable and extremely useful works in creating an integrative vision of anxiety is the work of Rollo May, „The meaning of anxiety”, which we will frequently quote in the chapter on anxiety.Thus, the paper debates and analyzes the concept of „ meaning and purpose in one's own life ” and how its existence or absence influences the individual's ability to live a state of mental balance.Throughout the paper, we will review the main approaches and theories on anxiety and depression in order to have a broader perspective on the evolution of their understanding both from the point of view of psychologically and in terms of inner life.We aim to highlight the usefulness and contribution of integrative existential analysis in psychotherapeutic support for addressing anxiety and depression.Methodological support for the connection between living the existential meaning, anxiety and depression will be addressed in the chapter destined for it by which we aim to analyze the connection between the three variables and the way they are influenced.